The effects of laser displacement on femtosecond laser-assisted conjunctival autograft preparation for pterygium surgery. - Valencia Hui Xian Foo; Yu-Chi Liu; Hon Shing Ong; Marcus Ang; Jodhbir S Mehta (PLoS ONE)
Aims To evaluate the effects of no-suction femtosecond laser (FSL) stability on conjunctival autograft (CAG) dissection in pterygium surgery. Methods Prospective analysis of 35 eyes from 34 subjects who underwent femtosecond laser-assisted pterygium surgery with the Ziemer Z8 laser (Ophthalmic Systems AG, Switzerland). Intraoperative absolute FSL displacements were measured and correlated with the duration and ease of CAG peel, CAG thickness, measured with intraoperative optical coherence tomography, and deviation from intended graft thickness. Results The median absolute FSL displacement was 22 μm (interquartile range [IQR] 14.7 to 60.8), while median vertical FSL displacement was 14.7 μm (IQR 7.3 to 44) and median horizontal FSL displacement was 22.0 μm (IQR 14.7 to 44). 65.7% had a grade 1 peel, 11.4% had grade 2 peel, 14.3% had grade 3 peel and 8.6% had grade 4 peel. The median duration of CAG peel was 5.4 seconds (IQR 3 to 21.4). The median CAG thickness was 69 μm (IQR 60.3 to 78.5), and the median deviation from targeted graft thickness was 9 μm (IQR 1 to 16). Eyes with more difficult peels and longer duration of CAG peels had significantly greater vertical FSL displacements (p = 0.04 and 0.02 respectively), but not horizontal displacement, age, ethnicity, CAG thickness or deviation from original thickness, compared to those with better quality and shorter duration peels. 1 eye (2.9%) had an incomplete CAG peel with a buttonhole and 2 eyes had graft tears (5.7%). Conclusion Micro-displacements during the suction-free CAG preparation are common but they did not affect the quality of the CAG peel, duration of peel, or CAG thickness. However, vertical globe displacement during FSL-assisted CAG creation was significantly associated with a more difficult and longer CAG peel duration. This highlights the importance of the cornea traction suture fixation to ensure stability of the eye during FSL application.